2015
DOI: 10.21829/azm.2015.3131088
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos registros de aberraciones cromáticas en el plumaje de dos especies de aves en zonas urbanas de Hidalgo y Tamaulipas, México/

Abstract: We report the first observations of partial leucism in Columbina inca and Quiscalus mexicanus, and also present the first record of albinism in Mexico for Q. mexicanus. We observed the leucistic individuals in human disturbed areas. This suggests that other individuals with chromatic aberration may be observed in non disturbed sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
1
0
4
Order By: Relevance
“…For example, in Ecuador partial leucism has been reported for the Ecuadorian Ground Dove (C. buckleyi) and total leucism in the Croaking Ground Dove (C. cruziana) (Cadena-Ortiz et al, 2015). In Chile, unspecified abnormal plumage for the Croaking Ground Dove was reported (Fuentes & González-Acuña, 2011); in Argentina albinism was reported in the Picui Ground Dove (C. picui) (Urcola, 2011) and in Mexico partial leucism and melanism have been reported in the Inca Dove (C. inca) (Rodríguez-Ruiz et al, 2015, Rodríguez-Ruíz et al, 2017. For the Ruddy Ground-Dove (C. talpacoti), schizochroism has been documented in Brazil (Missagia et al, 2016), ino aberration in Venezuela (Sainz-Borgo et al, 2016), while in Colombia, leucism was reported (Yusti-Muñoz & Velandia-Perilla, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Ecuador partial leucism has been reported for the Ecuadorian Ground Dove (C. buckleyi) and total leucism in the Croaking Ground Dove (C. cruziana) (Cadena-Ortiz et al, 2015). In Chile, unspecified abnormal plumage for the Croaking Ground Dove was reported (Fuentes & González-Acuña, 2011); in Argentina albinism was reported in the Picui Ground Dove (C. picui) (Urcola, 2011) and in Mexico partial leucism and melanism have been reported in the Inca Dove (C. inca) (Rodríguez-Ruiz et al, 2015, Rodríguez-Ruíz et al, 2017. For the Ruddy Ground-Dove (C. talpacoti), schizochroism has been documented in Brazil (Missagia et al, 2016), ino aberration in Venezuela (Sainz-Borgo et al, 2016), while in Colombia, leucism was reported (Yusti-Muñoz & Velandia-Perilla, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…La frecuencia de estas anormalidades parece ser más alta (1-2% vs. casi 0% en Passer domesti cus) en ciudades en comparación con las áreas rurales (Møller y Mousseau 2001), probablemente debido a que los factores que causan el leucismo son más comunes en áreas urbanas con mayor grado de contaminación (Møller y Mousseau 2001, Campos et al 2008. En México se ha observado una marcada relación entre los casos de anormalidades pigmentarias en áreas alteradas antropogénicamente (Rodríguez-Ruíz et al 2015). Esto muestra una tendencia creciente en la probabilidad de registrar individuos con plumajes de coloraciones anormales posiblemente por el estrés ambiental que ocasionan diversas actividades humanas como la urbanización, agricultura y ganadería (Rodríguez-Ruíz et al 2014).…”
Section: Discussionunclassified
“…En general se acepta que el leucismo no afecta el color del pico, de las patas ni de los ojos como sí sucede en el albinismo (Abreu et al 2013, Herrera 2017. No obstante, estas partes blandas pueden llegar a presentar ausencia de pigmento en presencia de leucismo (Rodríguez-Ruíz et al 2015).…”
Section: Introductionunclassified
“…O bien, ¿la determinación de la anormalidad pigmentaria ha sido la adecuada? Un caso donde se manejaron errores de identificación ocurrió con el albinismo de Q. mexicanus y el leucismo de C. inca (Rodríguez-Ruíz et al 2015), los cuales se debieron clasificar como aberración ino o envejecimiento por presentar plumas envejecidas o descoloridas por luz solar, con aberración marrón en otras plumas (H. van Grouw com. pers.).…”
Section: Discussionunclassified